No longer endemic to Africa: Kribiodosis Kieffer, 1921 (Diptera, Chironomidae) new to Oriental China with a phylogeny and expanded adult generic diagnoses - Han, Wu; Liu, Jie; Luo, Yifan; Tang, Hongqu (Zootaxa, 2021)
Kribiodosis Kieffer, 1921, an African genus of Chironomini (Diptera: Chironomidae), is newly recorded from the Oriental region through a new species K. cantonensis sp. n. Detailed descriptions of the male, female and a DNA barcode are provided. With the inclusion of the new species bearing scutal tubercle and fused tibial comb, the generic diagnosis needs revision and expansion. The phylogenetic position of Kribiodosis within the tribe Chironomini is explored based on five concatenated genetic makers (18S, 28S, CAD1, CAD4 and COI-3P) using both mixed-model Bayesian inference and maximum likelihood methods. Kribiodosis is placed as a core member of the Microtendipes group but its precise sister group remains unclear. Inclusion of the analysis of Nilodosis Kieffer, another Chironomini genus with an African-Oriental distribution, reveals an unexpected robust position as sister to a large and diverse inclusive group of many Chironomini.